Evaluation of Nurses’ Knowledge, Attitude, and Practice Regarding Nursing Process Implementation in a Tertiary Hospital - Chinna Chadayan; Nipul Mondal; Melba Sahaya Sweety (Adult Health Nursing Journal, 2026)
ABSTRACTBackground: The nursing process (NP) is a fundamental framework for delivering systematic, client-centered, and evidence-based nursing care that improves patient outcomes and healthcare quality. Despite its global recognition, implementation remains inconsistent, especially in low- and middle-income countries like Bangladesh, where limited data exist on nurses’ knowledge, attitudes, and practices related to NP.Aim: This study aimed to evaluate the knowledge, attitude, and practice of senior staff nurses regarding the nursing process and identify factors influencing its implementation at a tertiary-level hospital.Methods: A descriptive cross-sectional study was conducted among 132 senior staff nurses at a tertiary-level hospital. Data were collected via a self-administered structured questionnaire covering socio-demographic information, knowledge (20 items), practice (10 items), attitude (20-item Likert scale), and enabling/reinforcing factors (10 yes/no items). Descriptive statistics, chi-square tests, correlation, and regression analyses were performed to explore relationships among variables.Results: More than half of the nurses demonstrated average knowledge (53.0%) of the nursing process, with 34.1% showing good knowledge. However, poor practice predominated (60.6%), and attitudes were mostly uncertain (51.5%), indicating a disconnect between knowledge and practical application. Professional qualifications and experience significantly influenced knowledge, practice, and attitudes. Enabling factors such as institutional support and continuing education were identified as critical for NP implementation.Conclusion: The study revealed a significant gap between theoretical knowledge and practical application of the nursing process among nurses. Enhancing continuing professional development, improving workplace resources, and fostering positive attitudes through supportive leadership are essential strategies to promote effective NP implementation and ultimately improve nursing care quality in Bangladesh.